An improved sequential method for AC - Qifeng Ding
This paper reports the development of a novel and effective approach in AC/MTDC (multi-terminal DC) power system state estimation, called improved sequential method. The proposed approach is sequential in nature in which the MTDC system is solved followed by the AC system. Because the new method decouples the AC and MTDC systems without neglecting the coupling submatrices in the gain matrix, it exhibits good convergence characteristics. The variables and measurement equations of the MTDC system related to the problem formulation are discussed. The effectiveness of the proposed algorithm is demonstrated in this paper with extensive testing in several test systems and the results are compared with other state estimators. The main advantage of the method is that the proposed algorithm ran be used to easily adapt existing state estimation algorithm to cater for MTDC
Keywords: AC/MTDC power system state estimation; EMS; MTDC; Convergence; Coupling submatrices; Gain matrix; Improved sequential method; Measurement equations; Multi-terminal DC power system state estimation; Sequential method; State estimation algorithm; State estimators; Variables equations